Inhibition of sialidase activity as a therapeutic approach - Glanz VY; Myasoedova VA; Grechko AV; Orekhov AN (Dove Medical Press, 2018)
Victor Yu Glanz,1 Veronika A Myasoedova,2 Andrey V Grechko,3 Alexander N Orekhov2,4 1Department of Genetics, Cytology and Bioengineering, Faculty of Biology and Medicine, Voronezh State University, Voronezh, Russia; 2Laboratory of Angiopathology, Institute of General Pathology and Pathophysiology, Moscow, Russia; 3Federal Research and Clinical Center of Intensive Care Medicine and Rehabilitology, Moscow, Russia; 4Institute for Atherosclerosis Research, Skolkovo Innovative Center, Moscow, Russia Abstract: The demand for novel anti-influenza drugs persists, which is highlighted by the recent pandemics of influenza affecting thousands of people across the globe. One of the approaches to block the virus spreading is inhibiting viral sialidase (neuraminidase). This enzyme cleaves the sialic acid link between the newly formed virions and the host cell surface liberating the virions from the cell and maintaining the cycle of infection. Viral neuraminidases appear therefore as attractive therapeutic targets for preventing further spread of influenza infection. Compared to ion channel blockers that were the first approved anti-influenza drugs, neuraminidase inhibitors are well tolerated and target both influenza A and B viruses. Moreover, neuraminidase/sialidase inhibitors may be useful for managing some other human pathologies, such as cancer. In this review, we discuss the available knowledge on neuraminidase or sialidase inhibitors, their design, clinical application, and the current challenges. Keywords: sialidase, neuraminidase, neuraminidase inhibitor, influenza, drug design